Determination of the energy-optimal trajectory of a metro car based on solving a conditional minimization problem - Shtompel, Оleksandr; Khvorost, Mykola (Національний технічний університет "Харківський політехнічний інститут", 2025)
The paper proposes a method for determining the optimal trajectory of movement along a section of the metro car track to apply a method based on solving the problem of determining the optimal values of the speed limit for each section of the path. It is proposed that the energy consumed from the intermediate circuit can be chosen as a criterion for solving the conditional minimization problem. However, for the full identification of the parameters of the problem, it is necessary to determine the efficiency dependencies in the electric motor and traction drive as a function of the torque on the shaft and the rotational speed. An algorithm is proposed for determining the efficiency dependencies of the traction drive and traction synchronous motor, which takes into account power losses from higher harmonics of the traction inverter.

У роботі запропоновано якості методу визначення оптимальної траєкторії руху по ділянці колії метровагону застосувати метод на підставі вирішення задачі визначення оптимальних значень обмеження швидкості за кожною ділянкою шляху. Запропоновано енергію що споживається з проміжного контуру можливо обрати у якості критерію вирішення задачі умовної мінімізації. Однак для повної ідентифікації параметрів задачі необхідно визначити залежності ККД у електродвигуні та тяговому приводі як функції моменту на валу та частоти обертання. Запропоновано алгоритм визначення залежностей ККД тягового приводу та тягового синхронного двигуна, що враховує втрати потужності від вищих гармонійних тягового інвертора.
Визначення енергооптимальної траєкторії руху метровагону на підставі вирішення задачі умовної мінімізації
Keywords: subway car; traction drive; trajectory of subway train; traction motor efficiency; conditional minimization; вагон метрополітену; тяговий привод; траєкторія руху метропоїзду; ККД тягового двигуна; умовна мінімізація